Income Feasibility Analysis of Taro Farming on Peatland in North Singkawang District - Linda; Dolorosa, Eva; Oktoriana, Shenny (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
This research was conducted in Semelagi Kecil, Setapuk Besar, and Sungai Bulan villages in Singkawang Utara sub-district, Singkawang city, West Kalimantan province in 2023, using surveys and interviews with saturation sampling of 69 taro farmers on peatlands. This study aims to analyze and feasibility of taro farming on peatlands in North Singkawang District. The method used in this research uses a quantitative descriptive approach. The analysis used to calculate the feasibility of farming is by calculating the amount of revenue, total costs, income, R/C ratio, and BEP. This study shows the results that the feasibility of taro farming carried out in North Singkawang District is feasible to cultivate with farmers income of IDR 60,672,203 per hectare per growing season, total costs incurred 13,340,463 IDR/ha/growing season, with farmers income of IDR 53,829,109 per hectare per growing season, R/C ratio 4.55, and BEP production of 481.60 kg, BEP revenue of IDR 2,408,012, and BEP land 0.04 hectares. There is a need to increase farmers knowledge related to cultivation techniques, especially in the use of good and appropriate production inputs, so that the production inputs provided by farmers for taro farming are not less which can reduce production yields and not excessive which can cause waste of costs incurred.